Back Cover: Mapping the Free Energy of Lithium Solvation in the Protic Ionic Liquid Ethylammonuim Nitrate: A Metadynamics Study (ChemSusChem 15/2017). Issue 15 (1st August 2017) - Kachmar, Ali; Carignano, Marcelo; Laino, Teodoro; Iannuzzi, Marcella; Hutter, Jürg
Abstract : The Back Cover picture shows the free energy landscape for Li + solvation in ethyleammonuim nitrate (EAN). Using first‐principle simulations aided by a metadynamics approach, the solvation and transport of lithium in EAN was investigated. We identified different lithium solvation scenarios that were explored by the metadynamics and quantified their free energy barriers. The lowest free‐energy barrier appears to be consistent with what has been observed experimentally. More details can be found in the Full Paper by Kachmar et al. onpage 3083 in Issue 15, 2017 (DOI:10.1002/cssc.201700510 ).